Importance of bone health in bone lengthening - Christopher Iobst, MD, FAAOS, FAOA; Anirejuoritse Bafor, MBBS, FMCS, FMCOrtho, FACS; John E. Herzenberg, MD, FRCSC, FAAOS (Elsevier, 2024)
ABSTRACT: Distraction osteogenesis describes the process of growing new bone ("regenerate") to correct limb length discrepancies or limb deformities. Whether pure lengthening or a combination of lengthening and straightening is involved, this represents one of the highest anabolic demands on bone in orthopedic surgery. Because distraction osteogenesis requires the formation of new bone, often in large amounts, it is critically important to evaluate the bone health of any potential surgical patient. Patients undergoing limb lengthening, therefore, would be expected to be especially sensitive to poor bone health. This article will review opportunities to assess and potentially improve bone health for limb lengthening patients. Key Concepts: (1) Many potential limb lengthening patients may be vitamin D deficient or insufficient. (2) Other simple nutraceuticals such as Boron, Magnesium, Calcium, Silicon, vitamin K, L-arginine, and Inositol should be considered as adjuncts to bone health. (3) Intra-operative technique such as minimally invasive incisions that protect the blood supply and periosteum combined with osteotomies that maximize the bone surface area are recommended. (4) Numerous proposed pharmacological and mechanical interventions to improve and accelerate the healing of the regenerate bone look promising but are still investigational.